Construction and Validation of Novel Prediction Tools Based on Large Population-Based Database to Predict the Prognosis of Urachal Cancer After Surgery - Yu, Xiaowen; Ma, Chong; Wang, Maoyu; Ying, Yidie; Zhang, Zhensheng; Ai, Xing; Wang, Linhui; Zeng, Shuxiong; Xu, Chuanliang (Frontiers in Oncology, 2021)
Background: Urachal cancer is a rare neoplasm in the urological system. To our knowledge no published study has explored to establish model for predicting the prognosis of urachal cancer. The present study aims to develop and validate nomograms for predicting the prognosis of urachal cancer based on clinicopathologic parameters. Methods: Based on the data from the Surveillance Epidemiology, and End Results database, 445 patients diagnosed with urachal cancer between 1975 and 2018 were identified as training and internal validation cohort, 84 patients diagnosed as urachal cancer from 2001 to 2020 in two medical centers were collected as external validation cohort. Nomograms were developed using a multivariate Cox proportional hazards regression analysis in the training cohort, and their performance was evaluated in terms of its discriminative ability, calibration, and clinical usefulness by statistical analysis. Results: Three nomograms based on TNM, Sheldon and Mayo staging system were developed for predicting cancer specific survival (CSS) of urachal cancer, these nomograms all showed similar calibration and discrimination ability. Further internal (c-index 0.78) and external (c-index 0.81) validation suggested that Sheldon model had superior discrimination and calibration ability in predicting CSS than other two models. Moreover, we found the Sheldon model was able to successfully classify patients into different risk of mortality both in internal and external validation cohorts. Decision curve analysis proved that the nomogram was clinically useful and applicable. Conclusions: The nomogram model with Sheldon staging system were recommended for predicting the prognosis of urachal cancer. The proposed nomograms have promising clinical applicability to help clinicians on individualized patient counseling, decision-making and clinical and clinical trial designing.